EVALUATION OF THE ANTI – STAPHYLOCOCCAL ACTIVITY OF NAUCLEA ORIENTALIS LINN - Cruz, Jonas Preposi; M. Jubilo, Rose Merlyn (European Scientific Journal, ESJ, 2014)
Traditional medicine is becoming more popular nowadays. The use of herbal or medicinal plants is accepted in the health care system provided that there efficacy and safety were tested through research. This study determined the anti – staphylococcal activity of the mature leaves of Nuclea orientalis Linn. Results show that the crude alcoholic leaf extract of the mature leaves of Nauclea orientalis Linn. has an anti-staphylococcal activity. The 100 % extract’s anti-staphylococcal activity is comparable to Erythromycin. Furthermore, the formulated ointment from the 100% extract is also comparable to the wound healing efficacy of the Erythromycin ointment in terms of duration of healing. The findings show that Nauclea orientalis Linn. has antibacterial and pro-repairing actions.